MQTT Rancang bangun Server Message Queuing Telemetry Transport ( MQTT) Internet of Things ( IoT) Berbasis Eclipse - irwansyah irwansyah; Wahyuni Eka Sari; Agus Triyono; Yhunike Widiya Pratama; Muhammad Bagus; Bintang Tmur; susanna susanna (JSAI (Journal Scientific and Applied Informatics), 2025)
The design of a Message Queuing Telemetry Transport (MQTT) server for the Internet of Things (IoT) utilizes Eclipse Mosquitto as the core server software. The process begins with installation and basic configuration, including port setup, authentication, and encryption to ensure secure communication. Further customization is implemented to meet specific project requirements, such as configuring connection protocols, access permissions, quality of service (QoS) levels, and message retention policies. Integration with other Eclipse platforms, such as Eclipse Paho, supports the development of MQTT clients for IoT devices, enabling bidirectional communication between the server and devices. Additional tools like Eclipse Vert.x or Eclipse Hono may also be utilized to enhance device management and enable more complex message processing. Testing results indicate that the MQTT server implemented on a Raspberry Pi 3 B+ successfully received and transmitted data. The ESP32 device also achieved successful data communication via the MQTT server. The system can be accessed across different networks, offering flexible communication without reliance on the same local network. This implementation demonstrates the reliability of MQTT as a robust solution for IoT communication.